The Effect of Differences in Frequency of Feeding on the Growth and Nutrition of Black Soldier Fly Larvae (Hermetia illucens) - Rahayuning Tias, Esti
Industrial waste can be one of the environmental problems. Organic waste itself can be overcome through a bioconversion process, where the organic structure is converted into a more complex structure found in biomass from bioconversion agencies. One of the bioconversion agents that is currently being developed is Black Soldier Fly larvae (Hermetia illucens). H.illucens larvae can convert organic waste into body biomass with high nutrient content, making it possible to become an alternative protein source for various industrial needs. As it is the same process with breeding other animals, the frequency of feeding time can affect growth and nutrition content of the larval biomassa. Based on this matter, this study aims to determine the optimal feeding time of growth and nutrition content of H.illucens larval biomass. In this study, a mixture of fish waste and tofu waste with a ratio of 40%:60% are being used. During 20 days, the mixture is being fed to 5 different groups with a difference in feeding time which is once every 1 day (20 times), 3 days (6 times), 5 days (4 times), 10 days (2 times) and 20 days (1 time). The variables measured were the increase in average biomass of larvae and nutrient content of H.illucens larval biomass, the differences between each treatment were analyzed using the One-Way ANOVA test and Post Hoc Tukey test (P?0.05). The results showed the highest increase in average larvae (10.03 ± 1.34 mg / larva / day) (P?0.05) at the time of the study which the frequency of feeding is done 4 times (per 5 days). The nutrition of the larval biomass produced consisted of proteins of 44.79-50.39% and fat content of 10.44-16.32%. The conclusions obtained were the most optimal frequency of feeding once every 5 days (4 times), and the nutrient content of the biomass larvae contained the highest protein (50.39%) and the highest fat (16.32%) on treatment with the frequency of feeding once every 20 days (1 times).